A classification system for youth outpatient behavioral health services billed to medicaid - Rodríguez, Gabriela M.; Pederson, Casey A.; Garcia, Dainelys; Schwartz, Katherine; Brown, Steven A.; Aalsma, Matthew C. (Frontiers in Health Services, 2024)
GR, CP, KS, MA provided substantial contributions to the conception of the work. GR, CP, DG, KS, SB provided substantial contributions to analysis and interpretation of data for the work. GR drafted the work and CP, DG, KS, SB, MA revised it critically for important intellectual content. All authors provide approval for publication of the content and agree to be accountable for all aspects of the work in ensuring that questions related to the accuracy or integrity of any part of the work are appropriately investigated and resolved.